6-month multidisciplinary follow-up and outcomes of patients with paediatric inflammatory multisystem syndrome (PIMS-TS) at a UK tertiary paediatric hospital: a retrospective cohort study. (July 2021) - Penner, Justin; Abdel-Mannan, Omar; Grant, Karlie; Maillard, Sue; Kucera, Filip; Hassell, Jane; Eyre, Michael; Berger, Zoe; Hacohen, Yael; Moshal, Karyn; ,; Wyatt, Michelle; et al.
Summary: Background: Paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) is a new, rare, post-infectious complication of SARS-CoV-2 infection in children. We aimed to describe the 6-month outcomes of PIMS-TS. Methods: This retrospective cohort study comprised children (aged <18 years) who fulfilled the UK Royal College of Paediatrics and Child Health (RCPCH) diagnostic criteria for PIMS-TS and were admitted to Great Ormond Street Hospital (London, UK) between April 4 and Sept 1, 2020. Patients were followed up by a multidisciplinary team of specialists at 6 weeks and 6 months after admission. Biochemical and functional outcomes were analysed. Findings: 46 children were included in this study. The median age at presentation was 10·2 years (IQR 8·8–13·3), 30 (65%) patients were male and 16 (35%) were female, 37 (80%) were from minority ethnic groups, and eight (17%) had pre-existing comorbidities. All patients had elevated markers of systemic inflammation at baseline. None of the patients died. By 6 months, systemic inflammation was resolved in all but one patient. 38 (90%) of 42 patients who had positive SARS-CoV-2 IgG antibodies within 6 weeks of admission remained seropositive at 6 months. Echocardiograms were normal in 44 (96%) of 46 patients by 6 months, and gastrointestinal symptoms that were reported in 45 (98%) of 46 patients at onset were present in six (13%) of 46 patients at 6 months. Renal, haematological, and otolaryngological findings largely resolved by 6 months. Although minor abnormalities were identified on neurological examination in 24 (52%) of 46 patients at 6 weeks and in 18 (39%) of 46 at 6 months, we found minimal functional impairment at 6 months (median Expanded Disability Status Scale score 0 [IQR 0–1]). Median manual muscle test-8 scores improved from 53 (IQR 43–64) during hospital admission to 80 (IQR 68–80) at 6 months, but 18 (45%) of 40 patients showed 6-min walk test results below the third centile for their age or sex at 6 months. PedsQL responses revealed severe emotional difficulties at 6 months (seven [18%] of 38 by parental report and eight [22%] of 38 by self report). 45 (98%) of 46 patients were back in full-time education (virtually or face to face) by 6 months. Interpretation: Despite initial severe illness, few organ-specific sequelae were observed at 6 months. Ongoing concerns requiring physical re-conditioning and mental health support remained, and physiotherapy assessments revealed persisting poor exercise tolerance. Longer-term follow-up will help define the extended natural history of PIMS-TS. Funding: None.